Study of Sensitivity and Resistivity of Salmonella typhimurium Isolated from Patient and Cattle to the Antibiotics and It s Relation with Plasmids: Zainab Sami Habeeb ,Amal m. a. Al-Shawii - Habeeb, Zainab Sami (The Iraqi Journal of Veterinary Medicine, 2009)
The susceptibility of all Salmonella typhimurium isolates to the first line antimicrobial agents werestudied and the results obtained showed a variable sensitivity and resistivity since it shows e.gresistivity for human isolated were Ampicillin 100% ,Chloramphenicol 96% , Co-Trimoxazol 85%,Tetracycline 85%, Nalidixic acid 77% and Cefotaxime 33%, While in animal isolates they wereampicillin 57%, Co-Trimoxazol 14%, Chloramphenicol 26%, Tetracycline 42%, Nalidixic acid 85%and there was no resistant isolate to cefotaxime (0)%.Results obtained after the extration of the DNA plasmids revealed that acommon genetical bandshas been seen in addition to smaller ones that may differs in their appearance from astrain to anotheraccording to their antibiotic individual resistivity and sensitivity and this hypothesis may need a deeperand further studies to find prone relation .